República portuguesa, secularização e novos símbolos (1910-1926) - Leal, Ernesto Castro (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
We did select the historical perspective which involves the relations between the laical State and the Catholic Church, looking for deep marks of identity and national symbols, through the promotion of republican culturalʼs key objectives: republican citizenshipʼs rituals and political emblems; popular and civic participation on holidays and national parties; solidary ties between political republican memory and historical nacional memory construction.